Green Tea and Java Pepper Mixture Prevents Obesity by Increasing Energy Expenditure and Modulating Hepatic AMPK/MicroRNA-34a/370 Pathway in High-Fat Diet-Fed Rats - Jibin Kim; Dahye Han; Mak-Soon Lee; Jumi Lee; In-Hwan Kim; Yangha Kim (MDPI AG, 2023)
This study was performed to evaluate the anti-obesity effects of green tea and java pepper mixture (GJ) on energy expenditure and understand the regulatory mechanisms of AMP-activated protein kinase (AMPK), microRNA (miR)-34a, and miR-370 pathways in the liver. Sprague-Dawley rats were divided into four groups depending on the following diets given for 14 weeks: normal chow diet (NR), 45% high-fat diet (HF), HF + 0.1% GJ (GJL), and HF + 0.2% GJ (GJH). The results revealed that GJ supplementation reduced body weight and hepatic fat accumulation, improved serum lipids, and increased energy expenditure. In the GJ-supplemented groups, the mRNA levels of genes related to fatty acid syntheses, such as a cluster of differentiation 36 (CD36), sterol regulatory element binding protein-1c (SREBP-1c), fatty acid synthase (FAS), and stearoyl-CoA desaturase 1 (SCD1) were downregulated, and mRNA levels of peroxisome proliferator-activated receptor alpha (PPARα), carnitine/palmitoyl-transferase 1 (CPT1), and uncoupling protein 2 (UCP2), which participate in fatty acid oxidation, were upregulated in the liver. GJ increased the AMPK activity and decreased the miR-34a and miR-370 expression. Therefore, GJ prevented obesity by increasing energy expenditure and regulating hepatic fatty acid synthesis and oxidation, suggesting that GJ is partially regulated through AMPK, miR-34a, and miR-370 pathways in the liver.